Acceptability of 11 fortified balanced energy‐protein supplements for pregnant women in Nepal - Tsering P. Lama; Subarna K. Khatry; Sheila Isanaka; Katie Moore; Leslie Jones; Juliet Bedford; Joanne Katz; Saskia dePee; Steven C. LeClerq; James M. Tielsch (Maternal and Child Nutrition, 2022)
Abstract Evidence suggests that multiple micronutrient and balanced energy protein (BEP) supplementation during pregnancy can decrease the risk of stillbirth and small‐for‐gestational‐age births and increase birth weight. We conducted a mixed‐methods formative research study to identify the most acceptable among a range of 11 candidates fortified BEP supplements for use in pregnancy and lactation in a rural district in Nepal. Forty pregnant women aged 15–40 years participated in a test meal tasting of 11 different sweet and savoury candidate BEP supplements. Each participant rated the products on organoleptic properties using a 7‐point hedonic scale (1 = Dislike it very much to 7 = Like it very much), ranked her ‘top 3’ most liked supplements, and subsequently discussed each product with peers in focus group discussions (FGDs). Five supplements (sweet lipid‐based nutrient supplement (LNS), savoury LNS, sweet vanilla biscuits, vanilla instant drinks and seasoned pillows) achieved the maximum overall median hedonic score of 7, with sweet LNS and seasoned pillows ranking as the top 2. This was consistent with the assessments in FGDs. Women in the FGDs expressed dislike of the smell and taste of the cocoa drink, savoury masala bar, sweet mango bar and savoury curry biscuit, which was consistent with the hedonic scale scores. This study provides valuable insights into our understanding of women's acceptance of different BEP supplements during pregnancy in rural Nepal and has helped identify the two most accepted BEP supplements to be used in a two‐month home trial to assess utilisation and compliance in this setting.